THE IMPORTANCE OF PROFESSIONAL KNOWLEDGE IN TRANSLATION - Madaminova Madinabonu; Gafurova Nozima Ikramovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
ABSTRACT The primary aim of this paper is to highlight the significance of professional knowledge in translation. Additionally, it aims to encourage scholars to conduct additional research. The current trend among translators is the Professional theory of translation. Translators focused on the transfer of grammar, language meaning, and pragmatic linguistics in the Period of Linguistics Theory of Translation. Translators focused particularly on the transmission of cultural messages during the Period of Culture Theory of Translation, debating both readers-centered and authors-centered Domestication Translation strategies.